UV LUMINOSITY FUNCTIONS AT REDSHIFTS z ∼ 4 TO z ∼ 10: 10,000 GALAXIES FROM HST LEGACY FIELDS - Bouwens, R. J.; Illingworth, G. D.; Oesch, P. A.; Trenti, M.; Labbé, I.; Bradley, L.; Carollo, M.; van Dokkum, P. G.; Gonzalez, V.; Holwerda, B.; Franx, M.; Spitler, L.; et al. (The Astrophysical journal, 2015)
The remarkable Hubble Space Telescope (HST) data sets from the CANDELS, HUDF09, HUDF12, ERS, and BoRG/HIPPIES programs have allowed us to map the evolution of the rest-frame UV luminosity function (LF) from z ~ 10 to z ~ 4. We develop new color criteria that more optimally utilize the full wavelength coverage from the optical, near-IR, and mid-IR observations over our search fields, while simultaneously minimizing the incompleteness and eliminating redshift gaps. We have identified 5859, 3001, 857, 481, 217, and 6 galaxy candidates at z ~ 4, z ~ 5, z ~ 6, z ~ 7, z ~ 7, and z ~ 10, respectively, from the ~1000 arcmin super(2) area covered by these data sets. This sample of >10,000 galaxy candidates at z [> or =, slanted] 4 is by far the largest assembled to date with HST. The selection of z ~ 4-8 candidates over the five CANDELS fields allows us to assess the cosmic variance; the largest variations are at z [> or =, slanted] 7. Our new LF determinations at z ~ 4 and z ~ 5 span a 6 mag baseline and reach to -16 AB mag. These determinations agree well with previous estimates, but the larger samples and volumes probed here result in a more reliable sampling of >L* galaxies and allow us to reassess the form of the UV LFs. Our new LF results strengthen our earlier findings to 3.4[sigma] significance for a steeper faint-end slope of the UV LF at z > 4, with alpha evolving from alpha = -1.64 + or - 0.04 at z ~ 4 to alpha = -2.06 + or - 0.13 at z ~ 7 (and alpha = -2.02 + or - 0.23 at z ~ 8), consistent with that expected from the evolution of the halo mass function. We find less evolution in the characteristic magnitude M* from z ~ 7 to z ~ 4; the observed evolution in the LF is now largely represented by changes in [phi]*. No evidence for a non-Schechter-like form to the z ~ 4-8 LFs is found. A simple conditional LF model based on halo growth and evolution in the M/L ratio ([is proportional to](1 + z) super(-1.5)) of halos provides a good representation of the observed evolution.